A Project feasibility study on gemstone processing - Castillo, Althea O.; Evaristo, Alexander G.; Uy, Alvin T. (Diliman, Quezon City College of Engineering, 1995)
The Philippine Islands is very rich in natural resources. Among which are the semi-precious stones which may be transformed into various valuable items like pieces of jewelry. But in spite of the abundance of these gemstones, very few have ventured into this business because of the difficulties in identifying the stones or inadequate knowledge in their processing. Many of those who have gone into this are small-scale manufacturers and hobbyists. This paper contains a feasibility study on the processing of gemstones into semi-jewelry. The term "semi-jewelry" refers to a classification between bridge and costume jewelry. The finished product will be processed gemstones mounted on 10K gold. The feasibility study was divided into the following parts: Market Study, Technical Study, Financial Study and Socio-Economic Profitability. In the market Study, the objective was to confirm if there is indeed a demand for the product and ultimately to determine the market share that can be captured by the producer. To arrive at these figures, the jewelry industry was analyzed. As mentioned earlier, very few have ventured into this because of the lack of technical know-how and, moreover, because of the burdensome taxes that are imposed on the makers of these luxury items. As a result of the latter, many have remained unregistered in the Department of Trade and Industry and their transactions have remained unrecorded. Because of this, the supply of jewelry made by local manufacturers in the market cannot be accurately quantified. Data was gathered on jewelry that have been imported into the country but this quantity is also an inaccurate reflection of the supply of imported jewelry because of rampant smuggling activities. Thus, it was impossible to come up with a legitimate estimate of the supply of jewelry in the market and therefore we could not determine the unsatisfied demand for the product. To establish the demand for the product, an amount of income disposable for jewelry for the income brackets A and B, the target buyers of the product, was estimated. Expenses for jewelry was assumed to be 10% of the expenditure on the classification "Personal Care and Effects" in the Family Income and Expenditure Statistics. From the amount computed thereafter, a 1% share was targeted. This percentage was taken by considering the fact that it will be a new brand in the market and will, therefore, have to establish itself first. This amount will also be confirmed by the capacity estimated in the Technical Study. In the Technical Study, the objective was to estimate the total project cost. The total project cost is the sum of many factors such as plant location, production schedule and raw materials. There are various ways by which gemstones may be formed. They me be formed into cabochon; they may be faceted; or they may be beaded. It was decided to produce only pendants and earrings (both cabochon) and bracelets and necklaces (both beaded). The description of their processes and respective time estimates were given so that a schedule may be made. Manufacture of these stones required several machines and there are only two manufacturers of these machines which are MIRDC and Mr. Lother Steckel. Machines for cabochon making will be purchased from MIRDC and for beading from Mr. Steckel. Labor requirements were also determined after the number of machines to be purchased has been decided. Other expenses such as those for tools and equipments, for electricity, for water were estimated based on the desired production level. After all the pertinent costs have been estimated, the total production cost can be calculated. In the financial study, the objective was how to get funds for the project. The project contains only a minimum amount of fixed assets. Only the machineries and equipments will be fully owned, the rest such as land and transportation were rented and under installment. For this reason, only the machineries and equipments could serve as collateral for a loan. Majority of the project cost had to be funded in another manner. Financing was derived from two sources: a loan from the Development Bank of the Philippines, and the other is from owner's equity. Since the project is located within Metro Manila, the company was not given an income tax holiday. Nonetheless, most of the financial aspects or ratios were favorable and positive enough to conclude that the project is feasible.
Feasibility study
Submitted in partial fulfillment of the course requirements in IE 153 : Project Development and Management
Keywords: Precious stones; Jewelry; Participatory monitoring and evaluation (Project management)